The role of specific pancreatic antibodies in the differential diagnosis of complete clinical and laboratory remission of type 1 diabetes mellitus and MODY in children - E. A. Sechko; E. M. Romanenkova; I. A. Eremina; L. I. Zilberman; L. V. Nikankina; Z. T. Zuraeva; O. B. Bezlepkina; V. A. Peterkova; D. N. Laptev (Сахарный диабет)
BACKGROUND: T1D is characterized by autoimmune destruction of pancreatic β-cells, which develops due to genetic and environmental risk factors. Shortly after initiating the treatment with insulin, 80% of children with T1D may require smaller doses of insulin and develop clinical and laboratory remission of the disease so called «honeymoon». The issue of whether there is a need of differential diagnosis between autoimmune DM and non-immune forms of DM raises in cases of preclinical diagnosis of T1D and laboratory remission for more than 6 months.AIM: To study the clinical, immunological, genetic characteristics of T1D remission phase and MODY in children, to determine the diagnostic criteria for T1D and MODY in children.MATERIALS AND METHODS: A single-centre, cross sectional noncontrolled comparative study of two independent cohorts. Data of 150 children examined in the Endocrinology Research Center (January 2016–June 2021). First cohort included patients with complete clinical and laboratory remission of T1D (n=36), second cohort included patients with MODY, confirmed by genetic study (n=114).RESULTS: The median age of diabetes manifestation was significantly higher in patients with T1D — 11.25 years [8.33; 13.78] than in patients with MODY — 7.5 years [4.6; 12.2] (p=0.004). In patients with T1D remission the level of glycated hemoglobin was 6.0% [5.6; 6.4], in group with MODY — 6.5% [6.2; 6.7] (p<0.001). Patients with monogenic diabetes had impaired fasting glucose — 6.27 mmol/l [5.38; 6.72], while patients with remission phase had normoglycemia — 5.12 mmol/l [4.17; 5.87]. The oral glucose tolerance test was perform to all patients, two-hour glucose level did not significantly differ in two groups (p=0.08). A strong family history of diabetes in patients with MODY registered more often (93% vs. 66.7%). A positive autoantibody titer detected more often in patients with remission of T1D (77.8%) than in patients with MODY (11.4%). In addition, no more than 1 type of autoantibodies was detected in patients with MODY.CONCLUSION: Antibodies ZnT8 and IA2 showed the greatest significance for the differential diagnosis of T1D and MODY in cases with long absents of insulin requirement in children with diabetes mellitus. Genetic test is recommended in seronegative cases. If only one type of AT is detected, specialist should decide on the need to do diagnostic genetic test based on a comprehensive analysis of the patient’s clinic characteristics, including family history, manifestation and blood glucose levels.